Numerical assessment on floating stability limits for static vehicle under partial submergence - Al-Qadami, E.H.H. (Taylor's University, 2020)
Large debris including vehicles when swept by floods could threat peopleâs life and damage properties. Concerning vehicles in floodwaters, their stability remains a challenge to the research world, particularly the buoyancy depth and the parameters affecting them to float. Therefore, a detailed investigation of the forces and mechanisms leading to floating instability mode is of utmost importance. Herein feasibility of conducting a numerical assessment to define floating instability limits of static partially submerged flooded car has been conversed and validated. A simple scaled-down car model was used with dimensions of 14.2 cm length, 5.2 cm width, and 4.5 cm height. The model was placed inside a closed box with dimensions of 35 cm length, 18.5 cm width, 5.5 cm height and with six degrees of freedom toll under the given hydrodynamic characteristics, velocity and water depth for inlet, 0 pressure with 0 fluid fraction for free top, walls for bottom and sides. The results showed that the car model started to float when the flood depth inside the box reached 1.275 cm. Further, the said approaches showed good agreement with the overall error of < 2. The outcomes of this study can be used to assess any car models in terms of floating instability mode without the need to conduct laboratory experiments. Â© School of Engineering, Taylorâs University